Diseño y construcción de un equipo de subsolado profundo para la empresa palmas oleaginosas Bucarelia S.A. (2004)
This Project consists ofthe design and construction ofan equipment ofsub soiling deep to resist the problemsofcompactation ofthe soil, which appear in the plantations ofAfrican Palm-tree ofthe Company "PalmasOleaginosas Bucarelia S.A. " Based on international norms and with the study ofthe mechanical and othersproperties ofgrounds oftheplantation; the design ofthe Tool was mathematicallyformulated. This mathematiemodel used programs based on finite elements lilre: Solid Edge V-ll Academic Copy, Dynamic DesignerMotion and COSMOSDesignSTAR 3. O. The construction was validated in the pursuit ofthe models and underprocedures ofmanufacture. The tests ofthe equipment are based on practical standards, and proceduresestablished by the ASAE. This work looksfor to be the beginningofthe activities ofthe group ofdevelopmentofMeehanical Systems, ofthe school ofMechanical Engineering ofthe Industrial University ofSantander.